The Phenomenon Of Cultural Meaning In The Relationship Between Consultant And Client Of "Fengshui" Consulting - Bintang NURIJADI; Sunarto SUNARTO; Jamalullail JAMALULLAIL (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to understand the meaning and find the cultural concept of "Feng Shui" in the concept of spatial planning practices of Chinese communities in Indonesia. This study uses a phenomenological approach regarding the meaning and cultural values of "feng shui" in the spatial planning practices of Chinese communities in Indonesia. The research findings indicate that there is symbolic interaction in interpersonal communication between consultants and service users (patients). In this study, researchers collected data using observation and in-depth interviews to obtain research results. The research results obtained by researchers are the symbolic interactions that occur in the "feng shui" culture in the spatial practice of Chinese community buildings in Indonesia which have several stages, namely actions, namely consultant service users accept the presence of "feng shui" in their midst because it brings damage positive for the community, gestures that is, people interpret the movements of the practice of "feng shui" when possessed by spirits from gods who are trusted to provide solutions, significant symbols, namely symbols contained in the practice of "feng shui" which can be seen from the tools used during practice, mind in the process of consulting the practice of "feng shui" is closely related to symbols and language reflected in how the symbols and language that "feng shui" consultants use to service users and vice versa, self is the ability to self-reflect each individual from the assessment of the point of view or opinion of others.